Nanocomposite toughness, strength and stiffness: role of filler geometry. Issue 1 (February 2015) - Greenfeld, Israel; Wagner, H. Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> The toughness, strength and stiffness of nanocomposites are considered for the general case of hollow fillers with arbitrarily shaped cross-sections. The particular cases of nanotubes, thin wall general cylindrical fillers, and thin ribbons are examined. The toughness is expressed by the energy dissipated when the filler pulls out from the matrix during the composite fracture, taking into consideration the filler critical length. The study reveals how the properties of nanocomposites can be optimized by modulating the filler shape and dimensions, as well as the mechanical properties of the material and interface. The tradeoffs between toughness, strength and stiffness are analyzed in view of their different and sometimes opposite dependence on the material and geometric parameters. It is shown that when the filler is shorter than its critical length, typical of most current nanotubes, the toughness, strength and stiffness can be improved simultaneously by reducing the filler cross-sectional aspect ratio (wall thickness divided by diameter). The mechanical performance of composites reinforced by carbon nanotubes and microfibers is compared for several possible filler packing conformations, demonstrating the high potential of nanoreinforcement.